Information seeking behavior among public library users: Understanding nature of information searching - A. W. V. ATHUKORALA (Journal of Advanced Research in Social Sciences and Humanities, 2021)
Aim: The information user’s perception of a need drives their pursuit of information, which in turn causes their demands for formal and informal information sources and services, with the latter ultimately leading to success or failure. People actively seek out information and use it to complete their tasks. The public library’s goal as piece of information is to serve the community’s information needs. As a result, the public library’s primary function is to meet the informational and cultural requirements of the community at large through the information of materials and services applicable to a wide range of audiences and formats. In most cases, the local, regional, or national community, or the national government, is responsible for establishing, promoting, and funding the Public Library. Methodology: The purpose of the research is to gain insight into the habits of library users in Kalutara, Horana, Sri Lanka. The study population comprises users who frequent the main library and three satellite locations. Non-probability sampling through the convenience sampling strategy was used to select participants in this survey-based study. There was an 87% participation rate (n = 348).Findings: The results of this study show that many public library users are part of younger demographics and are students by profession. Most students in the study also regularly used the Horana metropolitan area public library. Therefore, most of their internet research is focused on school-related topics, such as those covered in class. Thus, library programs can be tailored to different demographics of young people. Implications/Novel Contribution: This research shows that the way information is discovered and the public library’s accessibility are negatively impacted by the library’s lack of resources. Current research indicates that public library administrations will put in place mechanisms to improve patrons’ access to information by modernizing reading services, updating books, expanding existing capacity, recruiting new service members, and providing electronic learning resources. Staff members must be educated appropriately to create a pleasant customer service environment. As a result of this study, we will have a much better grasp of what public library patrons are doing when looking for information. This would be useful for researchers in pinpointing methodological holes they can fill with future investigations.